Analisis Integritas Akademik dan Pemanfaatan Teknologi AI dalam Keberhasilan Pendidikan Digital - Nazwa Hanifah; Dinda Audia Syahira; Alfa Rizi Azhari; Abdul Kholik Nasution; Nurbaiti Nurbaiti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The rapid development of artificial intelligence technology, particularly through the use of language models such as ChatGPT, has brought about significant changes in educational practices in Indonesia. The use of this technology has contributed to the creation of a more efficient learning process while enriching students' abilities to master and understand material more comprehensively. However, the use of AI in academic activities presents a number of problems, particularly related to scientific integrity, including an increased risk of digital plagiarism and a decline in critical thinking skills. In view of these developments, this study focuses on examining how the use of ChatGPT affects academic integrity and the quality of digital learning at UIN North Sumatra. This study applies a descriptive qualitative method, in which data is collected through interviews with five students from the Faculty of Economics and Islamic Business (FEBI) to gain a deeper understanding of their perceptions of the use of artificial intelligence in learning activities. The findings show that although ChatGPT provides convenience and efficiency in the learning process, students emphasize the importance of supervision and knowledge of ethics so that this technology can be used appropriately and responsibly. Therefore, universities need to strengthen digital literacy and ethics among students and increase supervision to ensure that the use of this technology does not compromise academic integrity. This research contributes to a deeper understanding of the impact of AI use on academic integrity in Islamic universities in Indonesia.